Adsorption of SO2 and H2S by sonicated raw eggshell. (2020) - Ahmad, Waseem; Sethupathi, Sumathi; Kanadasan, Gobi; Iberahim, Nursashabila; Bashir, Mohammed J.K.; Munusamy, Yamuna
Abstract: In this study, raw eggshell was sonicated in presence of N, N-dimethyl-formamide (DMF) and tested for its capacity to adsorb SO2 and H2 S. The flow rate was kept constant at 300 ml/min throughout the study. Sonication was carried out at different temperature (30 °C, 60 °C and 80 °C) with a constant contact time of 3 h. It was found that sonication at higher temperature (80 °C) had the best adsorption capacities for both SO2 (2.4 mg/g) and H2 S (1.85 mg/g) respectively. The BET surface area of sonicated raw eggshell particles was about 3.39 m 2 /g. The reading was higher compared to raw eggshell. Moreover, in the process study, the sorbents were tested with 40% of relative humidity and at 2 different reaction temperature i.e. 100 °C and 200 °C. Increasing the reaction temperature and the relative humidity in the inlet gas further increased the adsorption capacities for both SO2 and H2 S. The results show that sonicated eggshell particles can be valorised as sorbents for SO2 and H2 S.